Internal Control Weakness and the Asymmetrical Behavior of Selling, General, and Administrative Costs. (January 2022) - Kim, Jeong-Bon; Lee, Jay Junghun; Park, Jong Chool
Firms with internal control weakness (ICW) problems are less likely to provide managers with timely and precise information useful for internal resource management. The real options theory implies that managers in ICW firms, faced with information uncertainty, are more likely to postpone downward adjustments of slack resources by exercising an option to wait until more information about future business prospects becomes available. Based upon this theory, we hypothesize and find that selling, general, and administrative (SG&A) costs are stickier for ICW firms than for non-ICW firms. We also find that the effect of ICW on SG&A cost stickiness is primarily attributable to internal information control problems, and becomes weakened significantly after firms remediate previously reported ICW. This impact of ICW on SG&A cost stickiness is robust to controlling for the possible influence of omitted variables, accounting for potential endogeneity in the presence of ICW, and using a firm-specific measure of cost stickiness. Our results are consistent with the prediction of the real options theory in that poor information quality associated with ICW incents managers to postpone downward adjustments of SG&A resources until the information uncertainty is resolved.